Rough frictional contact of elastic thin layers: The effect of geometrical coupling. (1st June 2019) - Menga, N.
Abstract: The rough contact behavior of thin layers in the presence of interfacial friction is investigated by means of an innovative fundamental elastic solution. A certain degree of geometrical coupling between normal and tangential elastic field is found which, depending on the layer thickness, may lead to larger contact areas compared to the frictionless case. A specific focus has been devoted to investigate the behavior of the local quantities at the interface, in terms of both the displacement field and the gap distribution. We found that significant thinner gaps are predicted due to elastic coupling and frictional interactions, which may lead to larger hydraulic impedance of the contact interface. The latter result is specifically interesting for applications such as seals, where lubrication and leakage are the governing phenomena.